PENGARUH DIGITAL MARKETING DAN VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO FROZENFISH88 KOTA BENGKULU - Apriansyah, Raju; Islamuddin, Islamuddin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The aim of the research is to determine Digital Marketing and Product Variations on Purchasing Decisions at the Frozenfish88 Store, Bengkulu City. And to find out which factors most dominantly influence purchasing decisions. This research used quantitative methods on 150 respondents. The population used in this research was consumers of the Frozenfish88 Store in Bengkulu City and sampling in this research used a non-probability sampling technique. Based on the results of multiple linear regression, the regression equation Y = 5.905 + 0.314 (X_1) + 0.379 (X2) is obtained. The research results and hypotheses show that Digital Marketing and Product Variations have a partial or simultaneous positive effect on Purchasing Decisions. Keywords: Digital Marketing and Product Variations on Purchasing Decisions